Regionalitet i danske stednavne: med fokus på torp-, rød-, tved- og holt-navne - Eggert, Birgit (Hikuin, 2008)
Regionality in Danish place names with focus on torp-, rød-, tved- and holt-names By Birgit Eggert In the author’s opinion there is a connection between the four place-name types in ‑torp, ‑rød, ‑tved and ‑holt, when we are talking about distribution, age and their situation in settlement history. All the four name types belong to the Viking Age and the Middle Ages. The torp-names reflect a new colonization of the mother town’s land, as well as reclamation of new land. The clearing names in ‑rød and ‑tved must reflect colonization of woodland, as the holt-names also do. But where the clearing names signify that the wood has been removed, the holt-names tell either of the former wood that existed before the clearing or that people moved into the wood without clearing it. The four place-name types are all inter-Nordic phenomena which spread out over the national borders. The names in ‑torp are found in all the Nordic countries as well as in the Viking colonies in the Danelaw and Normandy, but with a huge concentration in Denmark and in the southern part of Sweden. The rød-names are found mainly in the south and east of Denmark, as well as in Sweden and Norway, while the tved-names are found further west in Denmark, the Danelaw and Normandy as well as in Norway. But in Sweden there are only very few tved-names. The holt-names on the other hand are found in large numbers in all the Scandinavian countries, but like the rød-names they are absent from the Danelaw and Normandy. None of the four name types are thus typical just for Denmark, and therefore their regionality has to be seen in a larger perspective than a national one.